2003
DOI: 10.1080/0953710031000092839
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation in a circulating flow loop: combined effects of shear stress and exposure time

Abstract: Measurement of small changes in platelet activation state (PAS) in circulating stenotic systems in vitro has been problematic because of a paucity of real-time assay methods and circulation systems of low platelet-activating potential. PAS was measured by a modified prothrombinase assay in which activated platelets provide the essential cofactors in the activation of prothrombin by factor Xa. Chemical modification of the prothrombin ensures that the thrombin produced, while assayable, does not activate platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
111
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 18 publications
4
111
1
Order By: Relevance
“…We have previously shown that PAS measurements correlate with flow cytometry of negative-phospholipid exposure measured by annexin V binding. 15 Informed consent was obtained from healthy adult volunteers of both sexes who had taken no aspirin or ibuprofen for two weeks. Blood, 30 ml, was drawn by venipuncture and collected into 0.3 ml 40% trisodium citrate.…”
Section: In Vitro Platelet Activation State (Pas) Assay Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that PAS measurements correlate with flow cytometry of negative-phospholipid exposure measured by annexin V binding. 15 Informed consent was obtained from healthy adult volunteers of both sexes who had taken no aspirin or ibuprofen for two weeks. Blood, 30 ml, was drawn by venipuncture and collected into 0.3 ml 40% trisodium citrate.…”
Section: In Vitro Platelet Activation State (Pas) Assay Measurementsmentioning
confidence: 99%
“…Blood, 30 ml, was drawn by venipuncture and collected into 0.3 ml 40% trisodium citrate. Platelet buffer was then prepared and circulation experiments performed according to methods described by Jesty et al 15 . Recirculation studies were conducted at Re = 300 in a recirculation flow loop (Fig.…”
Section: In Vitro Platelet Activation State (Pas) Assay Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 Activated, but not unactivated, platelets contribute 2 essential cofactors in this reaction, negative phospholipid and factor Va. Thus, the rate of thrombin generation reflects the activation state of the platelets.…”
Section: Platelet Activation State Assaymentioning
confidence: 99%